Mapping the experiences of adult cancer patients receiving chimeric antigen receptor T-cell (CAR-T) therapy: A scoping review protocol - Isabela Girleanu; Anne-Marie Brady; Vanessa Boland (PLoS ONE, 2025)
Introduction Chimeric antigen receptor T-cell (CAR T) therapy is an advancement in cancer treatments, particularly for patients with haematological malignancies who have exhausted conventional therapies like chemotherapy and stem cell transplant. CAR-T therapy involves genetically engineering a patient’s own T-cells to attack cancer cells. The development of CAR-T therapy increased survival rates in 30% to 80% of patients. Due to its novelty, CAR-T therapy can present unforeseen challenges that prolong the experience of living with cancer and its treatment journey. While CAR-T cell therapies have the potential to be curative, these innovative treatments are often accompanied by a significant symptom burden, primarily cytokine release syndrome (CRS) and immune effector cell associated neurotoxicity (ICANS). Methods and Analysis The Arksey and O’Malley framework and the population, concept and context (PCC) framework will guide the development of this scoping review. The population of this review is adults (18 years of age and older). The concept scoped is experiences of patients in the context of CAR-T therapy. CINAHL, Medline (EBSCO), PsycINFO, EMBASE and Web of Science will be searched, including grey literature. Screening and data extraction will be conducted by two independent researchers following the inclusion criteria and The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) checklist. The protocol has been registered on Open Science Framework on 13 th of May 2025. Study Status Record screening is currently ongoing and it is estimated to be completed by 21 st of July 2025. Data extraction is estimated to commence on 22 nd of July 2025 and to be completed by 4 th of August 2025. Results are to be expected on 15 th of August 2025. Dissemination of Findings Findings will be disseminated to relevant healthcare services electronically, through oral or poster presentations, conferences, congresses and publications.